A Review of Instruments Used to Predict Early Breastfeeding Attrition - Lewallen, Lynne Porter (2006)
Few women breastfeed for 6 months or longer, and many who stop breastfeeding do so in the early postpartum period. To increase the number of breastfeeding mothers, health-care providers need to identify women at greatest risk for early breastfeeding attrition. This integrative review describes instruments used to assess breastfeeding in the early postpartum period and reports the results of studies using these tools. The instruments are then evaluated for similarities in variables and usefulness for clinical practice.